“Not Scientific” to Whom? Laypeople Misjudge Manner of Death Determinations as Scientific and Definitive - Kukucka, Jeff; Famulegun, Oyinlola (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2024)
When someone dies unexpectedly, a medical examiner may perform an autopsy to determine how they died (i.e., manner of death). Recent studies found that cognitive bias can affect manner of death judgments, such that extraneous non-medical information may cause the same death to be judged as either a homicide or accident, which has significant legal ramifications. In response, leading medical examiners clarified that manner of death is “not scientific” and “often does not fit well in court.” Yet medical examiners often testify in court, and little is known about how fact-finders appraise their judgments. To address this gap, we conducted two experiments in which mock jurors read and evaluated a medical examiner’s testimony at a murder trial (modeled after the real-world case of Melissa Lucio), while varying the expert’s opinion (i.e., homicide or accident) and the defendant’s attributes (i.e., an affluent white or underprivileged Latina woman). Overall, participants rated the medical examiner’s testimony as highly scientific, credible, and convincing, and it strongly affected their verdicts and belief in the defendant’s guilt, irrespective of the defendant’s attributes. Moreover, participants unexpectedly rated the expert as even more credible if they ruled the death a homicide rather than an accident. Our data thus reveal a worrisome disconnect between how medical examiners characterize their judgments (i.e., as nonscientific and tentative) and how jurors appraise those judgments (i.e., as highly scientific and practically dispositive). We discuss ways to remedy this disconnect, including reforming death investigation practices to curtail bias and encourage standardization and transparency.